An assessment of clinician and researcher needs for support in the era of genomic medicine. (August 2014) - Savage, Sarah K; Ziniel, Sonja I; Stoler, Joan; Margulies, David M; Holm, Ingrid A; Brownstein, Catherine A
Aim: To assess clinicians' and researchers' past, current and anticipated future use of next-generation sequencing (NGS) and anticipated needs for support.Materials & methods: A web-based survey was conducted at Boston Children's Hospital.Results: Many clinicians anticipate that they will use exome/genome sequencing (44.8%) and/or candidate gene panels (50%) within the next year. Researcher respondents anticipate the need for exome/genome sequencing (48.0%) and candidate gene panels (31.8%). Few respondents (13.6%) said that they felt 'Completely Ready' or 'Pretty Much Ready' to incorporate NGS into their clinical practice or research.Conclusion: Researchers and clinicians anticipate increased utilization of NGS. Respondents indicated varying degrees of need for a diverse list of support services, ranking interpretation and clinical correlation support as the most needed services.